Actuators: Improving and Predicting Fluid Atomization via Hysteresis‐Free Thickness Vibration of Lithium Niobate (Adv. Funct. Mater. 8/2018). (19th February 2018) - Collignon, Sean; Manor, Ofer; Friend, James
Abstract : A counterintuitively superior method for the efficient atomization of viscous fluids is described by James Friend and co‐workers in article number1704359 . Hysteresis‐free thickness vibration of lithium niobate is successfully implemented in a handheld nebulizer. The method could find wide‐spread application in pulmonary drug delivery, mass spectrometry, and liquid chromatography.